Depresi pada Pasien Diabetes Melitus Tipe 2 - Jenarut, Yohana Fransisca; Tania, Elly; Suparto; Ingkiriwang, Elly (Universitas Kristen Krida Wacana, 2024)
Patients with diabetes mellitus have a 2-3 times higher risk of experiencing depression compared to the general population, which can potentially exacerbate their overall health condition. This literature review aimed to investigate the prevalence of depression among type 2 diabetes mellitus patients and to identify its associated risk factors. This literature review was conducted by searching electronic databases including Google Scholar, PubMed, and ProQuest. Twelve studies met the inclusion criteria and were included in the analysis. The results revealed that the prevalence of depression among type 2 diabetes mellitus patients varied from 23.20% to 83.80%, with a majority of cases classified as mild to moderate. To identify risk factors contributing to the high prevalence of depression in type 2 diabetes mellitus patients, additional studies were explored. Based on this literature review, it can be concluded that the prevalence of depression among type 2 diabetes mellitus patients is quite high. Several consistently identified risk factors include advanced age, female gender, low education level, unstable or unemployed work status, low income, marital status, and longer duration of diabetes. Early detection and appropriate management of depression in individuals with type 2 diabetes mellitus are essential for enhancing quality of life and optimizing treatment outcomes.